2014
DOI: 10.1021/jf503846z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cytochalasins from the Endophytic Xylaria sp. and Their Biological Functions

Abstract: Bioassay-guided fractionation of the fermentation extract of Xylaria sp. XC-16, an endophyte from Toona sinensis led to the isolation of two new cytochalasans cytochalasin Z27, 1, and cytochalasin Z28, 2, along with three known compounds seco-cytochalasin E, 3, and cytochalasin Z18, 4, and cytochalasin E, 5. The structures of 1 and 2 were elucidated by spectroscopic and electronic circular dichroism methods. Compound 5 was shown to be potently cytotoxic against brine shrimp (LC50 = 2.79 μM), comparable to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…3−6 Therefore, there is an urgent need to develop new 35 antifungal agents to control those crop diseases effectively. One strategy to develop new antifungal 36 agents is to search for biologically active substances or lead compounds from plant secondary 37 metabolites, which has been proven to be effective and practicable for new pesticides of agricultural 38 field 7 and new drugs of medical field. 8 39 Euphorbia prolifera Buch-Ham., belonging to the Euphorbiaceae family, is a perennial herbaceous 40 plant distributed mainly in southwest China.…”
Section: Introductionmentioning
confidence: 99%
“…3−6 Therefore, there is an urgent need to develop new 35 antifungal agents to control those crop diseases effectively. One strategy to develop new antifungal 36 agents is to search for biologically active substances or lead compounds from plant secondary 37 metabolites, which has been proven to be effective and practicable for new pesticides of agricultural 38 field 7 and new drugs of medical field. 8 39 Euphorbia prolifera Buch-Ham., belonging to the Euphorbiaceae family, is a perennial herbaceous 40 plant distributed mainly in southwest China.…”
Section: Introductionmentioning
confidence: 99%
“…The 13 C NMR spectra of 1 (Table ) showed similar chemical shifts to that of cytochalasin D, especially of the macrocyclic ring moiety (Zhang et al . ). Further, it was concluded that 1 has the same configuration of cytochalasin D, and its structure is determined as 7‐keto,19,20‐epoxycytochalasin and named jammosporin A ( 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…These include the stereochemistry of the macrocyclic ring, with a trans C-8/C-9 junction and a cis C-4/C-9 junction and the a-orientation of Me-22 and the E configuration of the C-13/C-14 double bond. The 13 C NMR spectra of 1 (Table 2) showed similar chemical shifts to that of cytochalasin D, especially of the macrocyclic ring moiety (Zhang et al 2014). Further, it was concluded that 1 has the same configuration of cytochalasin D, and its structure is determined as 7-keto,19,20-epoxycytochalasin and named jammosporin A (1).…”
Section: Xylaria Longipes (Ay909015)mentioning
confidence: 88%
“…), cytochalasins (Zhang et al . ) and xylaranol B (Chen et al . ) are produced by members of the genus Xylaria , the largest and the most diverse genus in the Xylariaceae.…”
Section: Introductionmentioning
confidence: 99%